Effect of row spacing and nitrogen fertilization on growth, yield and composition of bulb in garlic (Allium sativum L.) cultivars - Dhaka, I S Naruka, R S (Journal of Spices and Aromatic Crops, 2001)
The field experiment to study the effect of row spacing and nitrogen fertilization on growth, yield and composition of bulb in garlic cultivars was conducted during rabi in 1998-99 and 1999-2000. All growth parameters, yield attributing traits, bulb yield and contents of the bulb increased significantly with the increasing level of nitrogen application and row spacing and these were maximum with nitrogen application of 200 kg ha-1 and a row spacing of 15 cm. However, the T.S.S. was higher in closer row spacing (10 cm). The cultivar, Jajavar local was significantly superior over the other two cultivars in all these characters. The interaction studies showed that the treatment combination of N. S2 V2, (Nitrogen @ 200 kg ha-1, row spacing of 15 cm and cultivar Jajavar local) gave higher bulb yield (128 q ha-1) with maximum net returns (Rs 77,236 ha-1) and a B : C ratio (3.06:1).